Poly (hydroxamic acid) ligand from cornstalk cellulose for heavy metal recovery from electroplating wastewater - Md Lutfor Rahman; Umi Aisyah Mahani; Kalsum Ahmad Mustamin; Mohd Sani Sarjadi; Sazmal Effendi Arsad; Shaheen M. Sarkar; Sandeep Kumar (Elsevier B.V., 2024)
In this study, a graft copolymerization was performed using the acrylic monomer onto cellulose derived from cornstalk. Thus, cellulose-graft-poly(methyl acrylate) (PMA) was prepared by a free radical reaction. Further, the poly(hydroxamic acid) ligand was created from PMA-grafting copolymer with hydroxylamine in an alkaline medium. Characterization techniques such as FT-IR, FE-SEM and thermogravimetric analysis (TGA) analysis were performed with the desired products such as cellulose, PMA-grafted cellulose and poly(hydroxamic acid). This study examined the performance of heavy metals removal from an aqueous solution using the poly(hydroxamic acid) ligand. The impact of several factors, such as pH, metal ion concentration and agitation period were studied using the batch adsorption approach of several metal ions (Cu²⁺, Fe²⁺, Co²⁺, Cr³⁺ and Ni²⁺). This ligand showed attractive sorption capacity with Cu²⁺ ions, obtained a maximal capacity of 331 mg g−1 at optimal pH 6. Among other metals also showed satisfactory adsorption capacity for Fe²⁺, Co²⁺, Cr³⁺ and Ni²⁺ were 290, 251, 230 and 210 mg g⁻¹, respectively. On the other hand, results demonstrated that adsorption by the poly(hydroxamic acid) ligand is regulated by the pH of the solution. The adsorption isotherm study is well explained by the Freundlich model with a high correlation coefficient value (R2 > 0.99). The experimental results suggest that the cornstalk cellulose-based poly(hydroxamic acid) ligand exhibits a heterogeneous surface, resulting in multiple layers formation on its surface. The heavy metals adsorption process followed the pseudo-second-order kinetic model (R2 > 0.997). This polymer ligand is capable of outstanding toxic metals removal magnitude, up to 90–98% from industrial wastewater. The implementation of a poly(hydroxamic acid) ligand derived from cellulosic materials as an adsorbent for metal ion extraction exhibits a promising approach.